2019
DOI: 10.1115/1.4045204
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Systemic Vascular Resistance Using Built-In Sensing From an Implanted Left Ventricular Assist Device

Abstract: This paper presents an approach for real-time estimation of the systemic vascular resistance (SVR) of heart failure patients who have a left ventricular assist device (LVAD). Notably, an approach is described that relies only on sensing that is built into the LVAD, so no additional sensors or measurements are required. The estimation of SVR is accomplished using a variant of the extended Kalman filter (EKF) algorithm, making use of a reduced-order systemic circulation model, and requires LVAD flowrate as an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In terms of the diseases cases, AS affects only the left ventricular pressure, the volume, and the flow rate at both in vitro and in silico data are in accordance with the physiological findings [25]. Vascular systemic resistance increment pulled up aortic pressure to 150 mmHg but did not affect the 𝑄 𝐿𝑉 (𝑡) value in all cases.…”
Section: A Pcae Modeling Simulationssupporting
confidence: 82%
See 2 more Smart Citations
“…In terms of the diseases cases, AS affects only the left ventricular pressure, the volume, and the flow rate at both in vitro and in silico data are in accordance with the physiological findings [25]. Vascular systemic resistance increment pulled up aortic pressure to 150 mmHg but did not affect the 𝑄 𝐿𝑉 (𝑡) value in all cases.…”
Section: A Pcae Modeling Simulationssupporting
confidence: 82%
“…On the other hand, Yang et al suggested an inverse problem for the seven parameters of the same model of ours together with Emax and Emin estimation based on nonlinear optimization assuming using the systemic arterial pressure [24]. The study given in [25] focuses only on vascular resistance change Rsys while [22]…”
Section: B Excitation Of Pcae By Critical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic changes in preload and afterload are sensed as forces against the magnetic pistons and trigger appropriate changes in piston cycling to automatically adjust hemodynamic support (8,9). Systemic vascular resistance is estimated to assist in patient monitoring (10). Preload sensitivity prevents potentially dangerous suction events and overpumping (8).…”
Section: Torvadmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] These inquiries underscore the importance of incorporating these CPs, enhancing our grasp of transient physiological dynamics. [20][21][22][23] Notably, when applying the extended Kalman filter (EKF) for physiological state estimation, model-based approaches are essential for handling unknown dynamics. However, EKF performance diminishes when nonlinear AV dynamics, especially during opening and closing, are absent.…”
mentioning
confidence: 99%